An Experimental Study on the Influence Solution Concentration and Nano-Additives on Cold Storage Performance of Tetrabutylammonium Bromide - Xiao Yang; Yuqi Ji; Haoyan Zhang; Bin Liu (Energies, 2024)
Tetrabutylammonium bromide (TBAB) is considered a promising alternative cold energy storage material. Due to the high dissociation heat of phase transition at an atmospheric pressure of 278–293 K, which reaches 200–500 kJ/kg, this substance is considered an effective cold energy storage medium for air conditioning systems. In this paper, the cold storage crystallization process of TBAB solution with different concentrations was tested by conducting experiments and the phase transition’s temperature and latent heat were measured. Finally, the growth characteristics of TBAB hydrate crystals with different concentrations (10%, 20%, 30% and 40%) were analyzed. Considering the cold storage temperature, phase transformation temperature and latent heat, the cold storage effect is the best when 40% TBAB solution is used. Although single substance phase change materials have a long service life, they have problems with low thermal conductivity and high undercooling. Therefore, researchers usually improve the performance of phase change materials by adding other auxiliary materials, thereby enhancing their application prospects. Among these auxiliary materials, adding nano additives to phase change materials can significantly improve latent heat, thermal conductivity and nucleation ability, while also reducing undercooling. Therefore, we studied the influence of different nano-additives (Al2O3, SiC, TiO2 and ZnO) on phase change materials. The composites with excellent properties were screened by cooling step cooling curve and differential scanning calorimeter (DSC). Compared with pure TBAB solution, the phase transition latent heat of the composite phase change materials (PCMs) prepared by adding nanoparticles were significantly increased. The results show that adding nano-SiC into 40% TBAB solution can obtain better performance. This work not only provides reference for the further research, but also a sight to design the phase change materials for the application of new phase change cold storage materials.